Impact of an intervention to support hearing and vision in dementia: The SENSE‐Cog Field Trial. (3rd December 2019) - Leroi, Iracema; Simkin, Zoe; Hooper, Emma; Wolski, Lucas; Abrams, Harvey; Armitage, Christopher J.; Camacho, Elizabeth; Charalambous, Anna Pavlina; Collin, Fideline; Constantinidou, Fofi; Dawes, Piers; Elliott, Rachel; et al.
Abstract : Objectives: Hearing, vision, and cognitive impairment commonly co‐occur in older adults. Improving sensory function may positively impact outcomes in people with dementia (PwD). We developed a "sensory intervention" (SI) to support hearing and vision in PwD. Here, we report the findings of an international open‐label field trial, and nested case series, to explore the impact of the SI on dementia‐related outcomes. Methods: This was a home‐based trial conducted in France, England, and Cyprus. Participants were people with mild‐to‐moderate dementia and hearing and/or vision impairment (n = 19) and their study partners (unpaid carers; n = 19). The "basic" SI included a hearing and vision assessment and provision of glasses and/or hearing aids. A subsample received the "extended" SI with additional weekly visits from a sensory support therapist (SST). Exploratory analyses of dementia‐related, health utility and resource utilisation outcomes were performed. Results: Quality of life (QoL) and sensory functional ability improved. Change in QoL exceeded the threshold for a minimum clinically important difference. There was a modest improvement (in absolute terms) post intervention in behavioural disturbance, self‐efficacy, and relationship satisfaction. Study partner time assisting instrumental activities of daily living (iADL) and supervision decreased by about 22 and 38 hours per month, respectively, although time for personal ADL support increased. Qualitative data supported effectiveness of the intervention: PwD were more socially engaged, less isolated, less dependent on study partners, and had improved functional ability and communication. Conclusions: These findings support the need for a definitive randomised controlled trial (RCT) to evaluate the effectiveness of the intervention.